A novel repression module, an extensive activation domain, and a bipartite nuclear localization signal defined in the immediate-early transcription factor Egr-1. - Gashler, A L (1993)
Egr-1 is an immediate-early response gene induced transiently and ubiquitously by mitogenic stimuli and also regulated in response to signals that initiate differentiation. The Egr-1 gene product, a nuclear phosphoprotein with three zinc fingers of the Cys2His2 class, binds to the sequence CGCCCCCGC and transactivates a synthetic promoter construct 10-fold in transient-transfection assays. We have analyzed the structure and function of the Egr-1 protein in detail, delineating independent and modular activation, repression, DNA-binding, and nuclear localization activities. Deletion analysis, as well as fusions to the DNA-binding domain of GAL4, indicated that the activation potential of Egr-1 is distributed over an extensive serine/threonine-rich N-terminal domain. In addition, a novel negative regulatory function has been precisely mapped 5' of the zinc fingers: amino acids 281 to 314 are sufficient to confer the ability to repress transcription on a heterologous DNA-binding domain. Specific DNA-binding activity was shown to reside in the three zinc fingers of Egr-1, as predicted by homology to other known DNA-binding proteins. Finally, nuclear localization of Egr-1 is specified by signals in the DNA-binding domain and basic flanking sequences, as determined by subcellular fractionation and indirect immunofluorescence. Basic residues 315 to 330 confer partial nuclear localization on the bacterial protein beta-galactosidase. A bipartite signal consisting of this basic region in conjunction with either the second or third zinc finger, but not the first, suffices to target beta-galactosidase exclusively to the nucleus. Our work shows that Egr-1 is a functionally complex protein and suggests that it may play different roles in the diverse settings in which it is induced.